Peranan Peraturan Daerah Terhadap Investasi - Ashary, Fatimah (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2016)
This study was conducted to determine the effect of local regulations in UU No. 25 Year 2007 about investing towards investment. The results of this study is that nearly 3,000 (three thousand) of local regulations hamper the investment, among others: (1). waste time, money, and energy to take care of the licensing business, (2). Make inefficient, (3). Potential misuse, (4). Investors are afraid to invest. The suggestions are: (1). The laws that inhibit must be canceled, (2). Enforcement of the manipulator improved, (3). Supervision improved, (4). Investors naughty refused entry, (5). Officials appointed to be trained in advance of excellent service to the investor.